Nitrogen fertilization rates affect quality and curing characteristics of tobacco during the harvesting period under field chilling stress - Ren, Ke; Wei, Zehui; Gu, Kaiyuan; Fu, Guorun; Zhang, Long; Zhang, Hong; Zhou, Bin; Chen, Feng; Chen, Yi; Simarani, Khanom; Hu, Binbin (Frontiers in Plant Science, 2025)
IntroductionField chilling stress during the maturation phase significantly impairs tobacco productivity and leaf quality. Nitrogen (N) management is a crucial agronomic approach for enhancing leaf quality and curing attributes; however, its specific role under chilling stress conditions remains poorly understood.MethodsField demonstrations employed ‘Honghuadajinyuan’ tobacco cultivar under varying N fertilization rates, i.e., T1 (18.9 kg N ha-1), T2 (27 kg N ha-1, conventional rate), and T3 (35.1 kg N ha-1) with uniform basal application of 15,000 kg ha⁻¹ composted farmyard manure. This study evaluated the quality characteristics of fresh and cured tobacco leaves, as well as the curing process, by integrating physical and chemical analysis with multivariate statistical approaches, including principal component analysis and multiple linear stepwise regressions.ResultsFresh tobacco quality, such as leaf tissue integrity, chloroplast pigment content, and antioxidant enzyme activities as well as curing characteristics (leaf moisture regulation capacity, pigment conversion efficiency, and antioxidant system stability) exhibited gradient pattern of T3 > T2 > T1, respectively. This trend was also reflected in carbon-nitrogen metabolic accumulation, economic traits, and sensory quality of cured tobacco leaves. T3 treatment application enhanced tobacco yield (7.35%) and economic value (43.97%) as compared to T2 treatment. Principal component analysis and multiple linear stepwise regressions revealed covariance structures among economic traits, sensory quality, and principal components F1 and F2 (R2=0.87, P<0.05). F1 (60.53% variance explanation rate) loaded predominantly on N fertilization rates and chloroplast pigments, whereas F2 (23.75%) exhibited strong factor loading with nicotine content, total N, and neochlorogenic acid content.ConclusionsIncreasing N fertilization by 30% above the conventional rate mitigates the adverse effects of field chilling stress, leading to significant improvements in yield and quality of mature tobacco.